Factors Influencing Quality of Life of Parents with Children Affected by Acute Lymphoblastic Leukemia: A Study at Childhood Cancer International Foundation, Jakarta - Trisya, Michelle; Tjhay, Francisca; Hasan, Surilena; Widjaja, Nelly Tina (http://dharmais.co.id/, 2023)
Background: The diagnosis and management of chronic diseases, such as Acute Lymphoblastic Leukemia (ALL), are significant for the quality of life of parents. In addition, several factors contribute to the quality of life of parents whose children battle ALL, including characteristics, duration of childcare, mental health, and family functioning. Therefore, this study aims to identify factors influencing the quality of life of parents whose children have ALL at the Childhood Cancer International Foundation in Jakarta. Methods: This cross-sectional study recruited 109 parents at the Childhood Cancer International Foundation as respondents. The assessment tools used included a Characteristics questionnaire, Self-Rating Questionnaire-20, APGAR Questionnaire, and WHOQOL-BREF questionnaire. Additionally, collected data were subjected to univariate, bivariate, and multivariate analysis. Results: Among the 109 respondents with an average age of 38 years and mean childcare duration of 28 months, 66.1% were females, 100% believed in God, 73.4% had partners, 47.7% possessed higher education, 83.5% earned below the regional minimum wage, 66.1% experienced mental health problems, and 11.9% had family dysfunction. Bivariate analysis showed a significant relationship between gender, mental health, and quality of life (p0.05). Multivariate analysis showed that marital status, education, economic status, and family functioning significantly correlated with quality of life. Conclusions: In conclusion, gender, marital status, education, economic status, mental health, and family functioning were found to exert a significant influence on the quality of life of parents raising children with ALL.